Game Edukatif Pengenalan Bahasa Wolio Berbasis Android - Nalis Hendrawan; Helson Hamid; Ahmad Gifar Dani (Jurusan Teknik Elektro Fakultas Teknik Universitas Halu Oleo, 2022)
Wolio is a regional language in the Baubau city area. Over time, this regional language experienced extinction. This happens to children because they are rarely introduced to the school environment due to the elimination of local content in the 2013 curriculum. In this study, we will introduce, educate and preserve through the Wolio language educational game which is more interesting and entertaining. This study involved students in grades 3,4 and 5 at SDN 2 Wameo as research subjects. Based on the results of observations, interviews, literature, and questionnaires using the Wolio language proficiency test questions for students. The data obtained 70% answered incorrectly and 30% answered correctly. This game is an Educational genre using the Multimedia Development Life Circle (MDLC) development method and can be run on the Android Platform. In testing the game using Alpha testing and Beta Testing conducted with 30 correspondents based on aspects of quality, functionality, efficiency, usability, and visualization, they received positive responses with an average percentage of 97% (very good and good) and 3% (poor and not good). good). Then after it was implemented in Game students, the average result was 94% answered correctly and 6% answered incorrectly.